Caste, culture, and hegemony : social domination in colonial Bengal - Bandyopādhyāẏa, Śekhara (Sage Publications, 2004)
It is widely believed that, because of its exceptional social development, the caste system in colonial Bengal differed considerably from the rest of India. Through a study of the complex interplay between caste, culture and power, this book convincingly demonstrates that Bengali Hindu society preserved the essentials of caste discrimination in colonial times, even while giving the outward appearance of having changed. Using empirical data combined with an impressive array of secondary sources, Dr Bandyopadhyay delineates the manner in which Hindu caste society maintained its cultural hegemony.